Community Profiling of Fusarium in Combination with Other Plant-Associated Fungi in Different Crop Species Using SMRT Sequencing - Walder, Florian; Schlaeppi, Klaus; Wittwer, Raphaël; Held, Alain Y.; Vogelgsang, Susanne; van der Heijden, Marcel G. A. (Frontiers in Plant Science, 2017)
Fusarium head blight, caused by fungi from the genus Fusarium, is one of the most harmful cereal diseases, resulting not only in severe yield losses but also in mycotoxin contaminated and health-threatening grains. Fusarium head blight is caused by a diverse set of species that have different host ranges, mycotoxin profiles and responses to agricultural practices. Thus, understanding the composition of Fusarium communities in the field is crucial for estimating their impact and also for the development of effective control measures. Up to now, most molecular tools that monitor Fusarium communities on plants are limited to certain species and do not distinguish other plant associated fungi. To close these gaps, we developed a sequencing-based community profiling methodology for crop-associated fungi with a focus on the genus Fusarium. By analysing a 1600 bp long amplicon spanning the highly variable segments ITS and D1-D3 of the ribosomal operon by PacBio SMRT sequencing, we were able to robustly quantify Fusarium down to species level through clustering against reference sequences. The newly developed methodology was successfully validated in mock communities and provided similar results as the culture-based assessment of Fusarium communities by seed health tests in grain samples from different crop species. Finally, we exemplified the newly developed methodology in a field experiment with a wheat-maize crop sequence under different cover crop and tillage regimes. We analysed wheat straw residues, cover crop shoots and maize grains and we could reveal that the cover crop hairy vetch (Vicia villosa) acts as a potent alternative host for Fusarium (OTU F.ave/tri) showing an eightfold higher relative abundance compared with other cover crop treatments. Moreover, as the newly developed methodology also allows to trace other crop-associated fungi, we found that vetch and green fallow hosted further fungal plant pathogens including Zymoseptoria triciti. Thus, besides their beneficial traits, cover crops can also entail phytopathological risks by acting as alternative hosts for Fusarium and other noxious plant pathogens. The newly developed sequencing based methodology is a powerful diagnostic tool to trace Fusarium in combination with other fungi associated to different crop species.